A U‐Th Dating Approach to Understanding Past Coral Reef Dynamics and Geomorphological Constraints on Future Reef Growth Potential; Mazie Bay, Southern Great Barrier Reef. Issue 2 (18th February 2020) - Leonard, Nicole D.; Lepore, Mauro L.; Zhao, Jian‐xin; Rodriguez‐Ramirez, Alberto; Butler, Ian; Clark, Tara R.; Roff, George; McCook, Laurence; Nguyen, Ai D.; Feng, Yuexing; Pandolfi, John M.
Abstract: Reconstructing coral reef histories provides a window of understanding into reef response to changing environmental and climatic conditions over various temporal scales. Here we present the results of 117 U‐Th dates from emergent reef flat and slope cores and surface death assemblages, combined with previously published fossil microatoll data, to capture the entire sequence of reef growth at Mazie Bay, inshore Southern Great Barrier Reef (GBR). Coral U‐Th dates indicate that Mazie Bay reef initiated 6, 900 years before present (yr. BP) quickly filling accommodation space. While rates of vertical reef accretion (5.3 ± 1.0 mm year −1 ) were comparable to the GBR average during the mid‐Holocene ( 5.0 mm year −1 ), reef flat progradation occurred at a rate 1.5‐ to 6‐fold previous GBR rates until 5, 100 yr. BP ( 70.4 cm year −1 ). Average progradation slowed to 7.1 cm year −1 in the subsequent 4, 000 years and reef slope cores indicate this reef had largely "turned‐off" by 400 yr. BP, with modern coral communities existing as a veneer over the largely senescent framework. Death assemblage dates highlight coral disturbance and recovery regimes in response to increased cyclone activity 1960–1985 AD and recent extreme sea surface temperature and flood events post 2000 AD. U‐Th dating of mid‐Holocene to modern coral deposits from Mazie Bay reef provides a unique insight into past reef development, response to recent disturbance regimes, and potential for future reef growth. In the case of Mazie Bay, our data suggest limited accommodation space and increased occurrence of sea surface temperature extremes will restrict future reef growth at this site. Key Points: The 117 coral U‐Th dates from Mazie Bay reef provide an insight into reef dynamics at multiple temporal scales Mazie Bay reef initiated 6, 900 yr. BP and rapidly filled optimum available accommodation space, with reef growth slowing by 4, 200 yr. BP U‐Th dating of death assemblages revealed quasi‐periodic cycles of disturbance and recovery over the past 60 years